Pengujian Black Box pada Sistem Informasi Praktek Kerja Industri (PRAKERIN) dengan menggunakan Metode Boundary Value Analysis - Muhammad Indra Rizaldi; Sandi Ramadhan; Mochammad Noor Holik Majid; Yulianti Yulianti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2020)
Praktek Kerja Industri (PRAKERIN) information system is a system used to record grades and other student data relating to the implementation of work practices in industry. This information system must be error free. If an error occurs can cause losses to stakeholders. To provide assurance that the information system developed has been free from errors, it is necessary to test. Testing is one level of the program implementation process that must be passed in order that an error can be found. Tests that can be said to be good are if the tests were initially found no errors and then errors can be found, even if only a small error. In testing the Praktek Kerja Industri (PRAKERIN) information system it is proposed as a Black Box. Black Box testing has various techniques. Of the many testing methods currently available, the current testing will use the Boundary Value Analysis method. The technique of determining the limits that exist in the lower and upper values to be able to produce the actual value. The test results show that the information system developed has been error free and has good quality.